The Impact of Facebook Advertising o Engagement Behavior: A Conceptual Paper - Shaouf, Abubaker A AB (University of Zawia Journal of Economic Sciences, 2024)
In today's digital age, Facebook has become an integral part of our daily lives, with millions of users worldwide spending a significant amount of time on Facebook. With the rise of Facebook usage, advertising has also become increasingly prevalent on this platform. This study aims to expend the Theory of Planned Behavior (TPB) to investigate the effect of Facebook ads on engagement behavior. Although the (TPB) is considered a robust method for studying actual behavior, it has been criticized for its limited explanatory power and failure to account for rational and emotional processes that influence human behavior. The conceptual model proposed in this study will contribute to understanding how Facebook ads influence engagement behavior in deferent contexts.